THE INFLUENCE OF COMMUNICATIVE METHOD ON THE FOREIGN LANGUAGE ACQUISITION OF CHILDREN - Isanova, Visola; Boymatov , Aziz (Журнал иностранных языков и лингвистики, 2023)
The majority of people believe that learning is best accomplished using a chalkboard and chalk. However, because the world today is dynamic and always changing, current educators must enhance their methods for teaching foreign languages to their students if they want them to learn the material more effectively. The growth of globalization makes it necessary to educate not just linguistic structures but also how to put them into practice. This article focuses on what is better for young people learning foreign languages.